INDUCTION OF TERMINAL HEAT STRESS TOLEREANCE IN CHICKPEA UNDER EXOGENOUS APPLICATION OF GROWTH PROMOTERS - A. Yasmeen; H. M. Muzamil (Journal of Animal and Plant Sciences, 2022)
High temperature stress has been measured as one of the crucial environmental features that adversely affect the plant growth and development. Therefore, a field experiment was carried out at Land Reclamation Research Station, 7/3-L Ahmad Pur Sial, Jhang, Pakistan to reduce the heat stress induced-losses to chickpea (Cicerarietinum L.) plants with the foliar spray of growth promoters during two consecutive years 2017-18 and 2018-19. Experimental treatments comprised of two chickpea cultivars (DHUST and Bhakkar 2011) cultivated on two different sowing dates (15th November and 1st December) and foliar spray of growth promoters (Benzyl-amino purine (BAP) and Moringa leaf extract (MLE30)) including tap water as a control. This study was laid out in a Randomized Complete Block Design (RCBD) with factorial arrangements having three repeats. Results suggested that high temperature stress severely reduced the chickpea growth and productivity. However, exogenous application of MLE had a tremendous effect on the studied attributes. Exogenous application of MLE improved the growth and yield contributing attributes, which ultimately increased the final productivity. Moreover, foliar spray of MLE produced significantly higher enzymatic antioxidants activitiesthat modulated the adverse impacts of heat stress on yield contributing traits. These results suggest that foliar spray of growth promoters particularly MLE modulated the heat stress induced losses to chickpea plants by improving their antioxidant defense mechanism and produced significantly higher grain yield during 2017-18 and 2018-19.
Keywords: Benzyl-amino purine; Moringa leaf extract; Catalase; Peroxidase; Grain yield